(untitled) (Research, Society and Development, 2020)
This study characterized socioeconomic, technological and productive aspects of fish farming in four municipalities in the Intermediate Geographic Region of Santarém, in the state of Pará, in order to guide public policies and private initiative actions for its development. 148 rural properties were visited between January 2018 and December 2019, for field observations and application of semi-structured forms to fish farmers or those responsible for managing the initiatives. The data obtained were tabulated in electronic spreadsheets and analyzed using descriptive statistics, being presented in tables and graphs. Fish farming is practiced mainly by producers with a low level of education and who started their activities less than 10 years ago. Among the fish produced, seven are native species, two non-native and one hybrid. The semi-intensive system was predominant and directed especially towards the monoculture of tambaqui Colossoma macropomum or of the tambatinga hybrid in nurseries excavated under direct population, that is, in a single phase. Most of the fish enterprises have flaws in the planning and in the productive and economic management, which, in addition to the difficulties of regularization, lack of training to act in the activity and technical assistance and high production costs, configure the main obstacles to the development of the activity in the region. It is recommended to review the state regulatory framework, improve technical assistance services, continue training for fish farmers and strengthen their social organization to overcome the obstacles identified, actions inherent to public power and private initiative, which tend to have little effect when performed in isolation.